Emigration preferences and plans among medical students in Poland - Krajewski-Siuda Krzysztof; Szromek Adam; Romaniuk Piotr; Gericke Christian A; Szpak Andrzej; Kaczmarek Krzysztof (BMC, 2012)
Abstract Background Migration and ethical recruitment of health care workers is receiving increased attention worldwide. Europe's aging population is creating new opportunities for medical doctors for finding employment in other countries, particularly those of a better standard of living. Methods We conducted a survey among 1214 medical students in five out of eleven universities in Poland with medical schools in October 2008. A series of statistical tests was applied to analyse the characteristics of potential migrants. Projections were obtained using statistical analyses: descriptive, multifactorial logistic regression and other statistical methods . Results We can forecast that 26-36% of Polish medical students will emigrate over the next few years; 62% of respondents estimated the likelihood of emigration at 50%. Students in their penultimate year of study declared a stronger desire to migrate than those in the final year. At the same time, many students were optimistic about career opportunities in Poland. Also noted among students were: the decline in interest in leaving among final year students, their moderate elaboration of departure plans, and their generally optimistic views about the opportunities for professional development in Poland. Conclusions The majority of Polish students see the emigration as a serious alternative to the continuation of their professional training. This trend can pose a serious threat to the Polish health care system, however the observed decline of the interest in leaving among final year students, the moderate involvement in concrete departure plans and the optimistic views about the opportunities for professional development in Poland suggest that the actual scale of brain drain of young Polish doctors due to emigration will be more limited than previously feared.